Noise Spectroscopy and Electrical Transport In NbO2 Memristors with Dual Resistive Switching - Nitin Kumar; Jong E. Han; Karsten Beckmann; Nathaniel Cady; G. Sambandamurthy (Advanced Electronic Materials)
Abstract Negative differential resistance (NDR) behavior observed in several transition metal oxides is crucial for developing next‐generation memory devices and neuromorphic computing systems. NbO2‐based memristors exhibit two regions of NDR at room temperature, making them promising candidates for such applications. Despite this potential, the physical mechanisms behind the onset and the ability to engineer these NDR regions remain unclear, hindering further development of these devices for applications. This study employed electrical transport and ultra‐low frequency noise spectroscopy measurements to investigate two distinct NDR phenomena in nanoscale thin films of NbO2. By analyzing the residual current fluctuations as a function of time, spatially inhomogeneous and non‐linear conduction are found near NDR‐1 and a two‐state switching near NDR‐2, leading to an insulator‐to‐metal (IMT) transition. The power spectral density of the residual fluctuations exhibits significantly elevated noise magnitudes around both NDR regions, providing insights into physical mechanisms and device size scaling for electronic applications. A simple theoretical model, based on the dimerization of correlated insulators, offers a comprehensive explanation of observed transport and noise behaviors near NDRs, affirming the presence of non‐linear conduction followed by an IMT connecting macroscopic device response to transport signatures at the atomic level.